213k views
4 votes
Thank you guys fir the help

Thank you guys fir the help-example-1

2 Answers

4 votes

Answer:


6 {x}^(3) - 2 {x}^(2) + 4x - 8

Answer C is correct

Explanation:


f(x) = 3 {x}^(2) + 4x - 6 \\ g(x) = 6 {x}^(3) - 5 {x}^(2) - 2 \\ (f + g)(x) =( 3 {x}^(2) + 4x - 6) + (6 {x}^(3) - 5 {x}^(2) - 2) \\ = 3 {x}^(2) + 4x - 6 +6 {x}^(3) - 5 {x}^(2) - 2 \\ = 6 {x}^(3) - 2 {x}^(2) + 4x - 8

User Vicente Bolea
by
6.9k points
5 votes

Answer:

6x^3-2x^2+4x-8

Explanation:

f(x) = 3x^2 +4x-6

g(x) = 6x^3 -5x^2 -2

f(x) + g(x) = 3x^2 +4x-6+ 6x^3 -5x^2 -2

Combine like terms

f(x) + g(x) = 6x^3+3x^2-5x^2+4x-6-2

=6x^3-2x^2+4x-8

User Oro
by
5.5k points